Malware analysis techniques : tricks for the triage of adversarial software - Barker, Dylan (Birmingham, UK : Packt Publishing, Limited, 2021)
This book is for incident response professionals, malware analysts, and researchers who want to sharpen their skillset or are looking for a reference for common static and dynamic analysis techniques. Beginners will also find this book useful to get started with learning about malware analysis. Basic knowledge of command-line interfaces, familiarity with Windows and Unix-like filesystems and registries, and experience in scripting languages such as PowerShell, Python, or Ruby will assist with understanding the concepts covered.
Section 1. Basic Techniques -- Section 2. Debugging and Anti-Analysis - Going Deep -- Section 3. Reporting and Weaponizing your findings -- Section 4. Challenge Solutions.
Includes index.
Keywords: COMPUTER SECURITY